The Implementation of the Circle Time Method in Islamic Religious Education (PAI) Learning at SDIT Ibnu Hajar Balikpapan - Asyadhili, Rifqi Hasan; Yusuf, Iskandar (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2023)
This article aims to provide a detailed explanation and analysis of the implementation of Circle Time in the context of Islamic Religious Education (PAI) at the Integrated Islamic Elementary School (SDIT) Ibnu Hajar in Balikpapan. The research background arises from the need to evaluate the impact of using the Circle Time method on the formation of students' characters. The primary focus is to determine if there is a significant difference in the development of students' characters after implementing the Circle Time method in PAI learning. This research is qualitatively directed through a case study approach. The research methods used involve in-depth interviews, careful field observations, and documentation analysis to collect comprehensive data. The data collection process is designed to provide a profound understanding of changes in behavior and the development of students' characters as a result of implementing Circle Time. The conclusions from observations and interviews indicate that Islamic Religious Education with the Circle Time approach has a positive impact on students' development. The role of the teacher is crucial, requiring motivation, patience, and mentoring skills to enhance the moral and religious values of children. Training on the Circle Time method is needed for the development of both teachers and students, serving as a foundation for continuous academic growth. With this training, teachers can enhance their ability to implement Circle Time, while students also receive its positive impact.